Olhares epifânicos - a epifania nos contos "Amor" De Clarice Lispector e “Á Sexta-Feira" de Luandino Vieira - Oliveira, Rosa de Souza (Africana Studia, 2020)
The literary macrosystem of Portuguese language o which Brazil and Angola belong allows the study of two feminine characters and also the magic of the "glance" into their moments of revelation. Clarice Lispector's tale "Amor" introduces Ana, alienated in her domestic world, which is the way she finds to avoid reflecting about her own self. Nela, from "À sexta-feira" by Luandino Vieira is also alienated. But her alienation is in the politicallevel, before the people's struggles to liberate Angola. The characters' alienation prevents them to be conscious of what is around them until the epiphany moment in their lives Iises up. This moment happens when both ofthem look in a different way at all their daily things. Ana "sees" a blind man chewing gum and Nela "sees" a woman oj cloths. Before, the characters used to see things, but without intentionally looking at them. This "glance" enhances the revelation moment of each one -the epiphany-, that brings their own self conscience.